Assessment of clinical and functional outcomes after single dose injection of autologous platelet rich plasma in patients with chronic lateral epicondylitis: a prospective and brief follow up study - Garg, Rohit N.; Patil, Hrishikesh; Mehta, Nirali; Bajaj, Sanket (International Journal of Research in Orthopaedics, 2023)
Background: Lateral epicondylitis is a chronic, painful, and debilitating elbow condition. The introduction of platelet-rich plasma as an adjunct to the conservative and operative treatment has revolutionized the research in this topic. PRP is considered to be the ideal autologous biological blood-derived product which helps in regenerating the degenerated tissue rather than just repairing it and helps in relieving pain and improving function. Methods: This is a prospective study where 40 patients diagnosed with tennis elbow, failing other conservative treatment modalities were enrolled; and treated with single dose injection of autologous PRP; and were evaluated for clinical and functional outcomes using the visual analogue scale and disabilities of arm, shoulder, and hand scores on the follow-ups. Results: Out of the 40 patients enrolled, there were 15 males and 25 females. The mean age of the population was 45.88±8.87 years. All the patients had improved statistically significant differences in mean VAS and DASH scores (p value<0.001) on each follow-up as compared to the baseline score with VAS score and DASH score improvement being more than 77% and 65% respectively at final follow up. Conclusion: Our study concludes that a single local injection of autologous PRP appears to be the promising and safe modality of treatment in lateral epicondylitis, helping to improve the pain as well as the clinical and functional outcomes.